The (Most) Algorithmic Animal: Unknowable Causal Structures in the Information Age - Bryson, Joanna J (Journal for the Cognitive Science of Religion, 2022)
Rituals are a means of regulation – they are a means for maintaining coherence and attaining long-term goals, including social coherence. But does their efficacy depend entirely, or at all, on their opacity? In this requested commentary on Harvey Whitehouse’s new book, The Ritual Animal, I discuss the utility of costly rituals in an evolutionary context, and suggest that causal opacity is only one, potentially substitutable cost. I relate this to the urgent topical concerns of polarization and of regulating sustainability globally.